PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER DISIPLIN DAN TANGGUNG JAWAB SISWA DI MI MISBAHUTTHOLIBIN LECES KABUPATEN PROBOLINGGO - Misbahul Munir (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
Discipline is a character that must be instilled in students from an early age, with thisdiscipline, students are always able to live independently when they have graduated orfinished studying. Discipline must also be emphasized at all levels of education inIndonesia.In addition to discipline, educational institutions must also emphasize an attitude of responsibility towards their students/students, because these two attitudes will later be interconnected with one another and cannot be separated. If someone does not have discipline and responsibility then he will be a loser.If these two characters are no longer emphasized in the world of education, then education in these institutions is considered to be experiencing a moral decline and students no longer have a sense of responsibility and a sense of self-discipline, so students start to be naughty, skip classes, and be lazy in teaching and learning activities. and less obedient to the orders of teachers and parents. From the problems above, the role of Islamic religious education teachers at MI Misbahuttholibin Kec.Leces, Probolinggo Regency can later form the character of discipline and responsibility for their students and can always know the inhibiting factors as well as the supporting factors in the formation of these two characters.The research we present is field research with aqualitative approach and data collection is carried out by observation and interviews as well as documentation which is one of the data collection techniques. In choosing data analysis the authors use data reduction and drawing conclusions.Keywords:Islamic Religious Education Teachers, Discipline Character and Responsibility.